Maternal high fat diets: impacts on offspring obesity and epigenetic hypothalamic programming - Harmancıoğlu, Begüm; Kabaran, Seray (Frontiers in Genetics, 2023)
Maternal high-fat diet (HFD) during pregnancy is associated with rapid weight gain and fetal fat mass increase at an early stage. Also, HFD during pregnancy can cause the activation of proinflammatory cytokines. Maternal insulin resistance and inflammation lead to increased adipose tissue lipolysis, and also increased free fatty acid (FFA) intake during pregnancy (˃35% of energy from fat) cause a significant increase in FFA levels in the fetus. However, both maternal insulin resistance and HFD have detrimental effects on adiposity in early life. As a result of these metabolic alterations, excess fetal lipid exposure may affect fetal growth and development. On the other hand, increase in blood lipids and inflammation can adversely affect the development of the liver, adipose tissue, brain, skeletal muscle, and pancreas in the fetus, increasing the risk for metabolic disorders. In addition, maternal HFD is associated with changes in the hypothalamic regulation of body weight and energy homeostasis by altering the expression of the leptin receptor, POMC, and neuropeptide Y in the offspring, as well as altering methylation and gene expression of dopamine and opioid-related genes which cause changes in eating behavior. All these maternal metabolic and epigenetic changes may contribute to the childhood obesity epidemic through fetal metabolic programming. Dietary interventions, such as limiting dietary fat intake <35% with appropriate fatty acid intake during the gestation period are the most effective type of intervention to improve the maternal metabolic environment during pregnancy. Appropriate nutritional intake during pregnancy should be the principal goal in reducing the risks of obesity and metabolic disorders.